2014
DOI: 10.1021/jo500696n
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific C–N Photocyclization of 2-Styrylquinolines

Abstract: Regiospecific C-N photocyclization of 2-styrylquinolines resulting in formation of potentially biologically active quino[1,2-a]quinolizinium derivatives was investigated. The presence of strong electron-donating groups in the phenyl ring reveals to be a crucial factor managing photocyclization effectiveness. Introduction of a crown ether moiety allows changing the photoreaction parameters by means of complexation with Mg(ClO4)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…[6] Monochromophoric 2SQ itself undergoes only transcis photoisomerization, [7] albeit entering electron-donor substituents into the styryl group promotes photocyclization. [8] The same effect, i. e. promotion of photocyclization, has a benzene ring annealing to quinoline nucleus. The angular annelation gives 3-styrylbenzo[f]quinoline (SBQ), whose de-rivatives (substituted in the styryl group) are able to the CÀN photocyclization.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[6] Monochromophoric 2SQ itself undergoes only transcis photoisomerization, [7] albeit entering electron-donor substituents into the styryl group promotes photocyclization. [8] The same effect, i. e. promotion of photocyclization, has a benzene ring annealing to quinoline nucleus. The angular annelation gives 3-styrylbenzo[f]quinoline (SBQ), whose de-rivatives (substituted in the styryl group) are able to the CÀN photocyclization.…”
Section: Introductionmentioning
confidence: 97%
“…It has been stated recently that the bichromophoric dyad with two 2‐styrylquinoline (2SQ) chromophores connected by an ortho ‐xylylene bridge undergoes [2+2] photocycloaddition with quantitative formation of a single rctt cyclobutane derivative . Monochromophoric 2SQ itself undergoes only trans ‐ cis photoisomerization, albeit entering electron‐donor substituents into the styryl group promotes photocyclization …”
Section: Introductionmentioning
confidence: 99%
“…Berdnikova and co-workers have developed a photochemical method to convert 2-styrylquinolines into quinolino[1,2-a]quinolinium derivatives (Scheme 52). 52 Irradiation of an acetonitrile solution of the starting material with a 125 W immersed mercury lamp initiated an E/Z isomerization and subsequent electrocyclization. Oxidative aromatization completed the cyclization, and addition of HClO 4 allowed for isolation of the perchlorate salt.…”
Section: Scheme 50 Photochemical Cascade For the Preparation Of Tetramentioning
confidence: 99%
“…We are developing regiospecific C–N photocyclization of hetarylphenylethenes resulting in the formation of charged polycyclic heteroaromatics. In this reaction, a new C–N bond is formed through the photoinduced electrocyclic ring closure followed by in situ oxidation of the resulting dihydrohetarene intermediate by air oxygen. The process takes place under mild conditions at room temperature, does not require the use of catalysts, and allows to obtain fused polycyclic cations with good yields.…”
Section: Introductionmentioning
confidence: 99%
“…The process takes place under mild conditions at room temperature, does not require the use of catalysts, and allows to obtain fused polycyclic cations with good yields. Recently, we have shown that the C–N photocyclization of 2-styrylpyridine and 2-styrylquinolines leads to the efficient and selective formation of benzo­[ c ]­quinolizinium derivatives. Notably, we performed the photogeneration of the DNA-binding 8,9-dimethoxybenzo­[ c ]­quinolizinium derivative 6 as a key process in a five-component supramolecular cascade.…”
Section: Introductionmentioning
confidence: 99%